THE NECESSITY OF APPLYING GREEN TECHNOLOGIES IN INDUSTRIAL ENTERPRISES (American Journal of Business Management, Economics and Banking, 2025)
In the modern era, the imperative of reducing environmental impacts while maintaining industrial productivity has led to the increasing adoption of green technologies in industrial enterprises. Green technologies, which focus on minimizing resource consumption, reducing emissions, and promoting sustainability, are key drivers in the global movement towards sustainable industrial development. This article examines the necessity of implementing green technologies in industrial enterprises, highlighting their role in improving energy efficiency, reducing environmental degradation, and ensuring long-term economic viability. The paper also discusses global best practices and outlines potential solutions for the challenges faced by industries in adopting green technologies.